Investigation of thermal characteristics of CNF-based nanofluids for electronic cooling applications - Zainal Abidin, Syazwani; Mohamad, Imran Syakir; Bani Hashim, Ahmad Yusairi; Abdullah, Norli; Md Isa, Mohamed Hafiz; Masripan, Nor Azmmi; Abdullah, Amirah (Universiti Malaysia Pahang, Malaysia, 2016)
A major problem being faced by existing coolants is the limited amount of heat that can be absorbed by the fluids. An innovative way to overcome this limitation is by utilizing a nano-coolant as a heat transfer medium in a cooling application. This paper was aimed at formulating an efficient nanofluid from Pyrograf III HHT24 carbon nanofibers (CNF) in a base fluid consisting of deionized water (DI) and ethylene glycol (EG) with polyvinylpyrrolidone (PVP) as the dispersant. The experiment was conducted by setting the variable weight percentage of CNF from 0.1 wt% to 1.0 wt%, with the base fluid ratio of 90:10 (DI:EG) weight percent. Then, the thermal properties of the formulated nanofluids were investigated. The test on the thermal conductivity of the nanofluids showed that the highest thermal conductivity of 0.642 W/m.K in this experiment was produced when the concentration of nanofluid is 0.5 wt% at a temperature of 40°C. Experimental investigations into the forced convective heat transfer performance of the CNF-based nanofluid in a laminar flow through a mini heat transfer test rig showed that the presence of nanoparticles enhanced the heat transfer coefficient as opposed to the original base fluid. The highest heat transfer coefficient was reported using nanofluid with a concentration of 0.6 wt% at 40°C. The enhancement of the heat transfer coefficient was due to the higher thermal conductivity value. The Nusselt number was also calculated and presented in this paper. This study showed that the CNF-based nanofluids have a huge potential to replace existing coolants in electronic cooling applications. Thus, in order to commercialize nanofluids in practice, more fundamental studies are needed to understand the crucial parameters that affect their thermal characteristics. Keywords: carbon nanofibers; nanofluid; thermal conductivity; heat transfer